LA TEXTUALIZACIÓN DE LA IDENTIDAD EN EL CINE DE PETER GREENAWAY. ANÁLISIS SEMIÓTICO DE THE PILLOW BOOK (1996) - Jesús HERNÁNDEZ LOBATO (Fonseca, Journal of Communication, 2023)
This paper aims to reassess Peter Greenaway’s filmography, in particular his acclaimed 1996 motion picture The Pillow Book, as a lucid reflection on the postmodern problem of textualized identities. By means of a thorough analysis of the sophisticated narrative, intertextual and aesthetical devices used in this film, this study identifies and interprets for the first time some particularly relevant visual clues, which give proof of a surprising depth and consistency as cinematic metaphors.